Colour pattern variation affects predation in chrysomeline larvae. (August 2016) - Tan, Eunice J.; Reid, Chris A.M.; Elgar, Mark A.
Abstract : Most animals are under strong selection to avoid predation, and several strategies have evolved in response to this selection. The developmental change in colour patterns of toxin-protected chrysomeline larvae provides a system to investigate the potential costs and benefits of conspicuous coloration development in animals. Field experiments in which artificial, palatable prey of various colour patterns were presented to wild avian predators confirmed that warning colours alone are not sufficient to deter predation, but that the spatial distribution of yellow and black coloration may be key to conferring a warning signal. Highlights: As Paropsis atomaria larvae develop, their black-patterned area increases. We tested the effect of black colour patterns on predation rates of larval models. Our results suggest that the absolute quantity of warning colours is insufficient. The spatial distribution of coloration may be key to conferring a warning signal.